Protokol Kesehatan EDUKASI DAN PRAKTEK PENERAPAN PROTOKOL KESEHATAN KB DIMASA PANDEMI : EDUKASI DAN PRAKTEK PENERAPAN PROTOKOL KESEHATAN KB DIMASA PANDEMI - Sari, Dian Nur Adkhana; Setyaningrum, Niken; Suryati, Suryati; Dharmawan, Ardian Indra (Ruang Ide Publisher, 2024)
Abstract The increasingly widespread COVID-19 pandemic requires everyone to be disciplined in implementing 3M's health protocols, namely wearing masks, maintaining physical distance, washing hands with soap and staying away from crowds. However, not everyone complies with these rules. Increasing knowledge as an effort to prevent the spread of Covid 19. This community service activity is carried out offline, before the Health Education is carried out, a pretest is carried out and a posttest is carried out in Health Education activities. After the education was carried out on health protocols for preventing Covid 19, there was an increase in knowledge among the audience, before the counseling was carried out 21 people (60%), 14 people (40%) after the counseling was carried out, knowledge about preventing Covid 19 increased for all respondents with a good category score of 35 people (100 %). Community service activities carried out with Health Education can increase knowledge and carry out good practices in implementing family planning protocols.